From Ontology to Anthropotechnics: Humanism, Media and Domestication of Being (Global Journal of Human-Social Science, 2020)
In this essay, we intend to approach how Peter Sloterdijk relates to the thinking of Martin Heidegger when questioning the humanist definition of man and proposing the notion of Anthropotechnics. To this end, the article begins by exposing Heidegger's conception of Technique and Humanism, and Ernst Jünger's influence on this issue. Then, when dealing with the question of being and ontological difference, the peculiar treatment that Sloterdijk offers to the ontological question is presented by articulating the history of being with a kind of genealogy of the clearing, bringing to the foreground certain intuitions of Friedrich Nietzsche about the beginnings of the human species. To conclude, Sloterdijk's thinking is developed, culminating in what he calls onto-anthropology, a notion presented in the work La Domestication de l'Être, and possible applications to issues related to biotechnology and contemporary media -which allows us to think a machinic history of being under the doubly complex bias of anthropology and ontology.
Keywords: onto-anthropology; anthropotechnics; domestication of being; humanism; post-humanism